A Historical Review of the Development of Electronic Textiles - Theodore Hughes-Riley; Tilak Dias; Colin Cork (Fibers, 2018)
Textiles have been at the heart of human technological progress for thousands of years, with textile developments closely tied to key inventions that have shaped societies. The relatively recent invention of electronic textiles is set to push boundaries again and has already opened up the potential for garments relevant to defense, sports, medicine, and health monitoring. The aim of this review is to provide an overview of the key innovative pathways in the development of electronic textiles to date using sources available in the public domain regarding electronic textiles (E-textiles); this includes academic literature, commercialized products, and published patents. The literature shows that electronics can be integrated into textiles, where integration is achieved by either attaching the electronics onto the surface of a textile, electronics are added at the textile manufacturing stage, or electronics are incorporated at the yarn stage. Methods of integration can have an influence on the textiles properties such as the drapability of the textile.